2017
DOI: 10.21037/acs.2017.08.05
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in Asia

Abstract: The use of transcatheter aortic valve implantation (TAVI) to treat severe symptomatic aortic valve stenosis has increased exponentially in the last decade. This rapid expansion was seen predominantly in Western developed nations and has been fuelled by favorable results reported from a plethora of well-publicized randomized controlled trials, large retrospective series and national registries. Now, TAVI has become the standard of care for inoperable patients and an alternative to open surgery in patients who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This useful tool can also assist physicians recognizing patients who would benefit from TAVR and other patients for whom SAVR may be the preferred treatment. TAVR in mainland China is rapidly evolving, and the most widely used commercial THV is currently the Venus A-valve ( 17 , 18 ). Therefore, the presented study may be an important step to bring this technology to Chinese physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This useful tool can also assist physicians recognizing patients who would benefit from TAVR and other patients for whom SAVR may be the preferred treatment. TAVR in mainland China is rapidly evolving, and the most widely used commercial THV is currently the Venus A-valve ( 17 , 18 ). Therefore, the presented study may be an important step to bring this technology to Chinese physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations in Europe and the US reported that TAVR had constituted almost half of AVR procedures ( 28 , 29 ). However, TAVR was commercially available in China after 2017, 5–10 years later than the western countries ( 30 ). In this nationwide survey conducted at the beginning of the TAVR era in China, TAVR accounted for only 11.3% (36/319) of total AVR procedures, and thus surgery remained the primary treatment for AS.…”
Section: Discussionmentioning
confidence: 99%
“…This useful tool can also assist physicians recognizing patients who would benefit from TAVR and other patients for whom SAVR may be the preferred treatment. TAVR in mainland China is rapidly evolving, and the most widely used commercial THV is currently the Venus A-Valve [17,18]. Therefore, the presented study may be an important step to bring this technology to the Chinese physicians.…”
Section: Validation Of the Modelingmentioning
confidence: 99%